Shaping the post-Soviet space? EU policies and approaches to region-building - Delcour, Laure (Ashgate Pub., 2011)
Drawing on a wealth of sources and extensive fieldwork conducted in the Commonwealth of Independent States (CIS), Laure Delcour questions the pursuit of this external objective and the existence of an EU regional vision in the post-Soviet area.